Brown Bear Ursus arctos Linnaeus, 1758 - Swenson, Jon E.; Ciucci, Paolo; Huber, Đuro; Penteriani, Vincenzo; Zedrosser, Andreas (Springer Nature, 2023)
This comprehensive species-specific chapter covers all aspects of the mammalian biology, including paleontology, physiology, genetics, reproduction and development, ecology, habitat, diet, mortality, and behavior. The economic significance and management of mammals and future challenges for research and conservation are addressed as well. The chapter includes a distribution map, a photograph of the animal, and a list of key literature.